TIPE-TIPE STOMATA TUMBUHAN FAMILI RUBIACEAE SEBAGAI BAHAN AJAR ANATOMI TUMBUHAN DI UNIVERSITAS LAMBUNG MANGKURAT BANJARMASIN - Alfina, Aulia; Amintarti, Sri; Widiyastuti, Dewi Amelia (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
Lambung Mangkurat University is home to a diverse range of plant species from the Rubiaceae family. This study aims to characterize several Rubiaceae species found at the university, located in Banjarmasin. Based on research by Stebbins & Khush (1961), the findings revealed that the only type of stomata observed across eight Rubiaceae species was of the parasitic variety. The species studied include Ashoka (Ixora paludosa L.) sp. 1, sp. 2, sp. 3, and sp. 4; Noni (Morinda citrifolia L.); Nusa Indah (Mussaebda frobodosa); Plate Glass (Gardenia augusta); and Coffee (Coffea sp.).